Becoming Australian: a review of southern Sudanese students' educational experiences. Issue 5 (4th May 2018) - Sellars, Maura; Murphy, Helen
ABSTRACT: This research presents a review of the literature around meeting students' learning needs in Australian schools. It is referenced to one group of students with refugee experience who have been in Australian schools for over 15 years; students with a background of oracy from Southern Sudan. The development of psychological health and literacy competencies are two of the most critical and complex responsibilities undertaken by education, and, in the case of these students two of the most significant when considered in relation to successful settlement, acculturation and assimilation. In presenting this literature, the bigger picture of how schools can fail, not only these students, but for any number of students from diverse backgrounds, becomes startlingly obvious, as do the ways in which the current political agenda inherent in the public education system in Australia privileges students of specific class and culture. Finally, recommendations are made regarding the development of policy and the concentration on pedagogical practices which acknowledge and respect the strengths and capabilities of this group of students.